UJI AKTIVITAS ANTI KOLONISASI BAKTERI ASAM LAKTAT DARI KEFIR SUSU KAMBING TERHADAP BAKTERI Escherichia coli PENGHASIL Extended Spectrum Beta Lactamase PADA USUS MENCIT BALB/c - Qurrata'yuni Pratiwi; Eustachius Hagni Wardoyo; Eva Triani (Faculty of Medicine Universitas Mataram, 2022)
Escherichia coli (E.coli) is a type of Gram negative bacteria species which is a normal flora in the digestive tract. However, it can potentially become pathogenic if the number in the digestive tract increases. E.coli infection can cause various inflammatory bowel diseases, such as IBD, Crohn's and ulcerative colitis (Khan et al., 2018). Several studies have found that probiotics can act as preventive and therapeutic agents to eradicate pathogenic bacteria through inhibition of adhesion and colonization. This study is conducted to determine the potential of BALB in inhibiting the colonization of ESBL-producing E.coli in vivo in BALB/c house mouse. The results of the in vivo colonization test show that BALB has good colonization inhibitory activity against ESBL-producing E.coli which is indicated by a decrease in the number of ESBL-producing E.coli colonies in pellet-induced BALB/c house mouse and CFS BAL.